A cyanine‐based dual‐modal probe for fluorimetric detection of mercury ion and colorimetric sensing of pH. (23rd March 2022) - Li, Yanjie; Qi, Youguo; Xu, Zhenxiang; Song, Yanxi; Li, Hongqi; Zhang, Jian; Tang, Junjie; Zhou, Jun
Abstract: A fluorescent probe derived from cyanine‐rhodanine conjugate was developed for dual detection of mercury (Hg 2+ ) ion and pH. Addition of Hg 2+ ion to the weakly fluorescent probe solution in dimethyl sulphoxide/water (DMSO/H2 O, 7:3, v/v ) induced discernible colour change and fluorescence enhancement while other metal cations including Li +, Na +, K +, Ag +, Cu 2+, Fe 2+, Zn 2+, Co 2+, Ni 2+, Mn 2+, Sr 2+, Ca 2+, Mg 2+, Al 3+, Cr 3+ and Fe 3+ did not cause obvious change in colour and fluorescence emission. The detection limit of the probe toward Hg 2+ ion is 1.61 × 10 −7  M. The probe also exhibited remarkable pH‐responsive effect. It acts as a dual chromogenic and spectroscopic probe for determining different pH scales over a wide range of pH 1.0–14.0: bright yellow with maximum wavelength ( λ max ) 416 nm for pH 1.0–2.0, orange with λ max 470 nm for pH 3.0–9.0, and pale yellow with λ max below 400 nm for pH 10.0–14.0. Plausible sensing mechanisms of the probe toward Hg 2+ ion and pH have been proposed.